Critical video engagements: Empathy, subjectivity and changing narratives of water resources through participatory video. Issue 90 (March 2018) - Tremblay, Crystal; Harris, Leila
Highlights: Reinforces potential of art interventions as tools for social transformation. Emotions, narrative, and subjectivity are critical for nature-society studies. Participants increased confidence from their ability to co-research. Participants expressed heightened senses of empathy and understanding for others. Participatory Video can open up new ways of understanding oneself as a citizen. Abstract: This article engages a critical feminist analysis of a community-based participatory video (PV) process focused on water and sanitation issues in underserved settlements of Accra, Ghana and Cape Town, South Africa. With focus on emotions and empathy, we highlight these concepts in relation to participant narratives and shifting subjectivities. In so doing, we consider how arts based engagement (in this case, through participatory video), might serve to foster new ways of relating to water resources and water infrastructures. The analysis highlights how the participants themselves reflect on PV as a vehicle for personal transformation, knowledge co-creation and a shifting sense of their own 'watered' subjectivity. We find that the PV process helps to uncover and identify knowledge and process gaps on by enabling individuals and communities—often unheard—to participate in civic and political debates around resource governance. While many positive elements were emphasized, we also suggest that there is a need for critical engagements that also address challenges associated with these methods, including limitations with respect to fostering fundamental long-term change in communities. In the conclusion, we broaden beyond our individual case studies to consider implications for community engagement and citizenship practices in the realm of natural resource governance.